O movimento discursivo nas rodinhas de crianças de 4 e 5 anos na Creche UFF - Brito, ângela Coelho de (2006)
The purpose of this dissertation is to demonstrate the discursive flow of children ranging from 4 to 5 years of age during the conversation-time circle in a public nursery school in Niterói, RJ. The study allowed us to understand the different aspects of the event and how meaningful they are for the daily life of the pre school and their importance for the pedagogic practice. The information selected for this study was obtained from two sources: the data collected during students talking time and a semistructured interview with the classroom teacher. Twenty-three instances were characterized based on what was said during ten different moments researched. The organizing actions were the most recurrent among the data analyzed, indicating that these circles are a highly-ordered activity affecting the not only the organization of the school routine but the relationship of all those involved in the activity, specially the children. The teacher has a relevant role in this organization, as it could be perceived from the high percentage of organizing interferences in her speech. The same attitude could be noticed from the participation of the other members involved: the trainee-teachers and the children. The analysis of the research allows us to conclude that the children are also deeply involved and interested in the organization of the educational space during the conversation-time circle.